Pedagogical ideas of Jan Amos Komeński - Jiří Pavlů (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2014)
The content of the article focuses on the presentation of the person and work of Jan Amos Comenius research in terms of Czech researchers of his legacy. The author discusses the most important ideas, beliefs and works of the said teacher proving timeliness of their content. The author encourages you to regularly reading and studying thoughts contained there, in order to find in them inspiration for the work of modern educators.